ACCEPTANCE OF OTHERS - AN INDICATOR OF PROSOCIAL BEHAVIOR - Vali ILIE (Universitaria Publishing House, Craiova, 2021)
The present study focuses on the analysis of prosocial behavior. The forms or subspecies of prosocial behavior, the compositional variables constituted in determining factors and its explanatory models are highlighted. The research part presents the answers of the students to the questions of a test regarding the acceptance of others, understood as a necessary condition in the development of prosocial behavior. The theoretical basis is a starting point in our constative research and it includes the results of certain investigations that are considered benchmarks in the study of this topic.